Transformations of an urban soil from the implantation of an agroforest - Dias, Maria (2023)
This study aimed to identify and understand the possible transformations occurred in an urban soil due to the implementation of an agroforestry in the Butantã campus of the University of São Paulo. To accomplish this objective, field surveys were carried out to study the soil of a grassy area and an agroforestry zone. Both areas share similar geomorphological and pedological conditions. The soil profiles were described morphologically, and samples were collected to perform physical and chemical analyses in the laboratory. The morphological attributes described in the field are: (i) color, (ii) texture, (iii) structure, (iv) wet consistency, (v) transition between horizons, (vi) depth, (vii) roots, and (viii) soil fauna. The following physical analyses were carried out in the laboratory: (i) grain-size, (ii) density, and (iii) aggregate stability. Finally, the main chemical parameters related to soil fertility were surveyed: pH H2O, pH CaCl2 0.01 mol L-1, O.M., P, K+, Ca2+, Mg2+, Al3+, H+Al, SB, CTC, V%, and m%. The results showed that the color of the surface horizon of the agroforestry area is browner than the analogous horizon of the grass area. In addition, an increase in the grade of the structure was identified in the soil of the agroforestry. The soil of this area also presents higher density of roots, which reach deeper horizons with respect to the grass area; ants and termites are absent (in contrast, they are very common in the grass area), but the presence of earthworms and beetles is common. The levels of soil density and acidity are smaller in the soil of the agroforestry. On the other hand, the O.M., P, K+, Ca2+, Mg2+ content and the SB, CTC, V% levels increased; only Al3+, H+Al, and m% decreased. Thus, we conclude that the identified soil changes in the agroforestry area suggest a recovery of soil and its functions faster than expected (1 year and 4 months), even in an urban soil whose natural conditions were deeply modified by anthropic actions.